A Novel Murine Chronic Obstructive Pulmonary Disease Model and the Pathogenic Role of MicroRNA-21 - He, Shengyang; Li, Liqiu; Sun, Shenghua; Zeng, Zhengpeng; Lu, Junjuan; Xie, Lihua (Frontiers in Physiology, 2018)
Chronic obstructive pulmonary disease(COPD) is a multi-pathogenesis chronic lung disease. The mechanisms underlying COPD have not been adequately illustrated. Many reseachers argue that microRNAs(miRs) could play a crucial role in COPD. The classic animal model of COPD is both time consuming and costly. This study proposes a novel mice COPD model and explores the role of miR-21 in COPD. A total of 50 wide-type(WT) C57BL/6 mice were separated into 5 equally-sized groups – (1) control group(CG), (2) the novel combined method group(NCM, cigarette smoke(CS) exposure for 28 days combined with cigarette smoke extract(CSE) intraperitoneal injection), (3) the short-term CS exposure group(SCSE, CS exposure for 28 days), (4) the CSE intraperitoneal injection group(CSEII, 28 days CSE intraperitoneal injection), and (5) the long-term CS exposure group (LCSE, CS exposure).The body weight gain of mice were recorded and lung function tested once once the modeling was done. The pathological changes and the inflammation level by hematoxylin eosin (H&E) staining and immunohistochemical staining(IHS) on the lung tissue sections were also evaluated. The level of miR-21 in the mice lungs of the mice across all groups was detected by RT-qPCR and the effects of miR-21 knock-down in modeled mice were observed. The mice in LCSE and NCM exhibited the most severe inflammation levels and pathological and pathophysiological changes; while the changes for the mice in SCSE and CSEII were less, they remained more severe than the mice in the CG. The level of miR-21 was found to be negatively correlated with lung functions. Moreover, knocking miR-21 down from the modeled mice, ameliorated all those tested COPD-related changes. Our novel modeling method detected virtually the same changes as those detected in the classic method in WT mice, but in less time and cost. Further, it was determined that the level of miR-21 in the lungs could be an indicator of COPD severity and blocking functions of miR-21 could be a potential treatment for early stage COPD.